Ownership Structure and Islamic Banks Performance: An Empirical and Multiregional Tests Before, During and after the Last Global Financial Crisis - Djeutcheu, Cedrix Ngandop (International Journal of Economics and Financial Issues, 2019)
This paper investigates the effects of ownership structure on Islamic Banks (IBs)’ performance in many regions (Middle East and North Africa, Europe, and others Asian countries), using agency theory as an analytical framework. The study period covers ten consecutive years (2006-2015), we use ROAA (Return on average Asset), ROAE (return on average Equity), and NIM (Net Income Margin) as measures of performance. Ownership structure was operationalized in terms of ownership concentration (percentage of share held by the top shareholder) and ownership identity (identity of the top shareholder). Results suggest almost no relationship between ownership concentration and IBs’ performance, before, during and after 2008/2009 financial crisis. Ownership identity may be linked to IBs’ performance, results suggest a positive and statistically significant relationship between Family-owned IBs and performance, Controlled IBs and Managerial IBs as well. Keywords: Ownership concentration, corporate governance, Islamic banks performance. JEL Classifications: G21, G32, G01 https://doi.org/10.32479/ijefi.7365